Functional dissection of a single enhancer at the mouse α-globin locus - Francis, H (2019)
Enhancers are cis-regulatory DNA elements that bind transcription factors and drive expression of target genes in a spatio-temporal manner. Despite their collective importance in cell fate specification, up to now enhancers have often been studied in assays that ignore the chromosomal context required for their function in vivo. In my DPhil, I aim to probe a single enhancer sequence in situ, using the strongest enhancer at the mouse α-globin locus as a model. The project addresses four main issues. Firstly, I test the sufficiency of a single element (R2) to activate gene expression when removed from its super-enhancer context. Impaired activation of the α-globin genes in this model highlights the importance of sequence context in enhancer function. Secondly, I describe the characterisation of an in vitro erythroid differentiation system to enable the analysis of novel genetic mutants of the α-globin locus. Thirdly, I present in vitro data from a number of informative enhancer combinations of the α-globin super-enhancer. Results support findings from the in vivo single-enhancer model and highlight a potential role for seemingly inactive elements in super-enhancer function. Finally, I zoom in from the level of a complete gene locus to that of a single 238 bp transcription factor binding platform at the core of the R2 enhancer, to determine the rules governing enhancer function at the sequence level. Ultimately, I aim to determine which of the models of transcription factor binding and element co-operation are most fitting at this locus and probe the principles of transcriptional activation.